Variations in Bacterial Community of Rearing Water and Gut of Common Dentex, Dentex dentex (Linnaeus 1758), Larvae Using Three Microalgae Management Approaches. Issue 5 (30th May 2017) - Giménez Papiol, Gemma; Roque, Ana; Estévez, Alicia
Abstract: Microorganisms present in the rearing water colonize the gut of first feeding larvae and represent the first barrier against opportunistic pathogens. The aim of the experiments presented herein was to standardize a protocol for the management of rearing water and microalgae suitable for the larval rearing of common dentex. In Experiment 1, bacteria–algae interactions were tested using a monospecific microalgal community, Tetraselmis chuii, suitable for nutritional experiments and with known antibacterial activity. In Experiment 2, the evolution of the bacterial community and larval performance (growth and survival) were monitored daily, in three conditions: (1) mature water: T. chuii was added 5 d before the rearing of common dentex larvae, (2) green water: T. chuii was added 1 d before, and (3) clear water: no T. chuii addition. The results show the influence of the presence of T. chuii on the evolution of the bacterial communities, both in terms of bacterial density and morphology, and indicate green water is the most suitable water treatment for management of larval rearing for common dentex.